PENGARUH PERSEPSI HARGA, LOKASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN YAMAHA SUKSES SEJAHTERA SILIWANGI SEMARANG - Hanifa Novitasari, 13.05.51.0051; Wuryan, Sophiyanto (Students Journal of Economic and Management, 2017)
This purpose of this study was to analysis the effect of perceived price, location and service quality to customer satisfaction of Yamaha Sukses Sejahtera Siliwangi Semarangâs customers. The population in this study were customers who made for minimal twice purchase of service at Yamaha Sukses Sejahtera Siliwangi Semarang. The number of samples studied were as many as 100 people were selected as respondents used purposive sampling technique. Data collection methods used in this study was questionnaire filled out by respondents. The analysis technique has been done by using validity test, reliability test,multiple linear regressions test, model feasibility test and hypothesis significance test.Data processing using SPSS Version 19th.The results of this study showed thatperceived price, location and service quality have positive effect and significant on customer satisfaction. Keyword: perceived price, location, service quality and customer satisfaction